Meta-analysis: The Influence of celebrity endorsements on Generation Z's Online Purchasing Decisions - Yolanda Veybitha; Sari Sakarina; Frecilia Nanda Melvani; Muhni Pamuji; Nur Resma Arianti (International Journal of Management and Business Economics, 2023)
Generation Z actively interacts on social media, namely TikTok and Instagram. This is an opportunity for business people to use the services of Instagram celebrities or TikTokers to influence their shopping behavior. The purpose of this review is to draw conclusions about how much influence endorsers have on the online shopping behavior of generation Z. Generation Z spends half of their time on social media. The author tries to review several studies both at home and abroad to draw generalizations regarding the role of endorsers in influencing the online shopping behavior of generation Z. The method used in this review is meta-analysis, which summarizes several studies over the last 10 years regarding the online shopping behavior of the generation. Z is influenced by celebgrams or tiktokers. The results of the review show that generation Z is more influenced by digital marketing, therefore it is advisable for business people to use Instagram celebrities, TikTokers or YouTubers if they want to use celebrity endorsements in their advertising.